Diagnostic accuracy of hematological parameters in Acute mesenteric ischemia-A systematic review. (June 2019) - Khan, Sualeh Muslim; Emile, Sameh Hany; Wang, Zhen; Agha, Muhammad Akbar
Abstract: Background: We conducted a systematic review on the diagnostic accuracy of classical and newly reported hematological parameters which are easily available in a resource limited setting in making a diagnosis of Acute Mesenteric Ischemia (AMI). Methods: We searched the PubMed, Scopus, and Cochrane library from January 1940 to April 2018. The search was limited to studies published in English and those involving human subjects only. The diagnostic accuracy of conveniently available parameters: Mean Platelet Volume (MPV), Neutrophil to Lymphocyte Ratio (NLR), Red Cell Distribution Width (RDW), lactate, D-dimer, alkaline aminotransferase, aspartate amino transferase, white blood cell count, lactate dehydrogenase, and amylase were assessed in this review. Studies were only included if they provided sufficient information allowing us to make a diagnostic accuracy contingency table and define a gold standard test. We excluded letters, editorials, and case reports. There were no restrictions to any particular study design. The QUADAS 2 protocol was used for quality appraisal. This study protocol was registered on Prospero with ID CRD42018088953. Results: Of 560 articles which were initially retrieved, 20 studies, comprising of 2043 participants, were eligible for this review. AMI was diagnosed in 518 patients. D-dimer had the highest median sensitivity of 93% while the median specificity of lactate and NLR were 85.9 and 85.8, respectively. Conclusion: Observing the high heterogeneity among the studies, currently it is difficult to suggest any single marker for diagnosing AMI. Compared to the classical markers, RDW, NLR and MPV showed higher specificities. Using these new markers alongside with the classical markers in the context of a scoring system might help in making a diagnosis of AMI in emergency settings. Highlights: Delay In diagnosis is a major modifiable risk factor for mortality in Acute Mesenteric Ischemia. Focused assessment of hematological parameters can be of significant help in stratifying those who are at greater risk. Clinical suspicion and hematological markers can help in emergency in considering a diagnosis of Acute mesenteric Ischemia.